Age and Gender Differences in Cardiovascular Autonomic Failure in the Transgenic PLP-syn Mouse, a Model of Multiple System Atrophy - Kermorgant, Marc; Fernagut, Pierre-Olivier; Meissner, Wassilios G.; Arvanitis, Dina N.; N'Guyen, Du; Senard, Jean-Michel; Pavy-Le Traon, Anne (Frontiers in Neurology, 2022)
Multiple system atrophy (MSA) is a rare and progressive neurodegenerative disorder. Autonomic failure (AF) is one main clinical feature which has a significant impact on health-related quality of life. The neuropathological hallmark of MSA is the abnormal accumulation of α-synuclein in oligodendrocytes forming glial cytoplasmic inclusions. Only little is known about gender and age differences in AF in MSA. This study was carried out in 6 and 12 months old transgenic PLP-α-syn and WT male and female mice. Heart rate variability (HRV) was assessed both in time, frequential and non-linear domains. Baroreflex sensitivity (BRS) was estimated by the sequence method. Duration of ventricular depolarization and repolarization (QT / QTc intervals) were evaluated from the ECG signals. Three-way ANOVA (genotype x gender x age) with Sidak’s method post-hoc was used to analyze data. BRS was significantly changed in PLP-α-syn mice and was age-dependent. QT and QTc intervals were not significantly modified in PLP-α-syn mice. An impaired HRV was observed at 12 months of age in PLP-α-syn female but not in male mice, indicative of cardiovascular AF.